International Migration Policies 2013 (Wall Chart) - United Nations Department of Economic; Social Affairs (United Nations, 2013)
The International Migration Policies 2013 wall chart provides up-to-date information on Government views and policies on international migration issues, including immigration, emigration, naturalization, and integration of migrants, for 193 Member and 3 non-member States of the United Nations. The wall chart also provides specific measures adopted to increase investment by the diaspora. In addition, the wall chart includes information on estimates of migrant stocks, share of females among international migrants, net migration rates, and remittances.